Futures of the furniture type lumber dryer through scenario building - Cortez, Rodrigo E. Jr (University of the Philippines Diliman, 2010)
The Furnace Type Lumber Dryer (FTLD) is the most commercialized technology for the Forest Products Research and Development Institute (FPRDI). But for the past 30 years it has not undergone significant improvements. In order to determine the technological needs of the furnace type lumber dryer and formulate strategies for its improvement, the scenario building process was conducted. The social, technological, economic, environmental and political aspects of the furniture industry in relation with the lumber dryer were done. A SWOT analysis was also conducted as a part of the environmental scan stage of the process. A focus group discussion was conducted to determine the key predictable variables and uncertainties that affect the technology. The variables and uncertainties were clustered and ranked. Market growth and resources were identified as the top ranked variables affecting the design of the FTLD. Three scenarios were created and analyzed. The scenarios that were created for the FTLD are the following : a) The Imported Look, wherein we look at a wood furniture industry facing high energy costs that abandons further developments of the local drying technology. b) The Makeover, wherein we see a wood furniture industry enjoying the benefits of low cost of energy, and c) Something for the old, wherein we see a furniture industry not solely relying on wood as primary source of raw material. The scenarios are assessed as to its coherence by identifying key turning points and vulnerabilities. Key turning points identified include government's poor or non-implementation of the provisions given under RA 9513, increases in R&D budget, and change in taste and preferences of global consumers by the year 2020. Vulnerabilities identified include high maintenance cost for the foreign dryers, prevalence of R&D budget cuts in 2020, and the slow implementation of the RE Bill. Strategies were formulated and a rough roadmap towards improving the technology was recommended for validation and improvement. Strategies include the triple helix, collaborative projects between DOST and other agencies, technology acquisition, and the development of measures to counter scenario vulnerabilities.